Justice and Regulation in Pharmaceutical Patents: A Comparative Philosophical Inquiry into India and Indonesia (1970–2024) - Raymond R. Tjandrawinata (Jurnal Impresi Indonesia, 2025)
This article traces the evolution of pharmaceutical patent regimes in India and Indonesia through a jurisprudential and philosophical lens, positioning justice, certainty, and protection as the three normative pillars of evaluation. The theoretical framework draws on John Rawls’s theory of distributive justice, Satjipto Rahardjo’s concept of progressive law, and Barry Mitnick’s theory of the political economy of regulation. Historical analysis reveals two epistemologically distinct trajectories. Since 1970, India has developed a legal system that balances exclusive rights and public welfare through substantive mechanisms such as Section 3(d), compulsory licensing, and drug price control under the National Pharmaceutical Pricing Authority (NPPA). Indonesia, by contrast, initially adopted a TRIPS-compliant positivist approach and began transitioning only in 2024 toward a more reflective and justice-oriented patent regime through the enactment of Law No. 65/2024 on Patents. The study argues that the fairness of a patent system should not be measured by its capacity to create monopolies of knowledge but by its effectiveness in distributing the benefits of technology to those most in need. It concludes with the formulation of a Balanced Patent Justice Framework (BPJF) a normative model integrating Rawlsian fairness, Satjiptian humanism, and Mitnickian institutional design to construct a pharmaceutical patent regime that is not only efficient but also morally sustainable.